Effect of slag basicity in ferromanganese production using medium-grade manganese ore from East Java-Indonesia. Issue 2 (3rd April 2018) - Nurjaman, Fajar; Saputra, Eka Bobby; Ferdian, Deni; Suharno, Bambang
ABSTRACT: Ferromanganese is one of the most important alloying elements in steel industries. In this work, the production of ferromanganese was carried out using three-phase submerged mini electric arc furnace. The effect of slag basicity due to the addition of a various amount of limestone as fluxing agent on this smelting process was investigated. The chemical composition of ferromanganese and slag was analysed with X-ray fluorescence. From this experiment, the optimum slag basicity was 0.8 that produced 8.2 kg of ferromanganese with 78.1% Mn, 12.7% Fe, and 8.9% Si. It resulted from 30 kg of manganese ore, 7.5 kg of cokes, and 12 kg of limestone.